DFPV - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
As a result of cooperation between the Dutch Government and the Permanent Interstate Committee for Drought Control in theSahel (CILSS) a Crop Protection Training Project (DFPV) was established in Niger. Initially known as the Department ofTraining...